Papua New Guinea Student Assesment : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2016)
This report focuses specifically on policies in the area of student assessment. Papua New Guinea has focused on increasing student learning outcomes by improving the quality of education in the country. An effective student assessment system is an important component of efforts to improve education quality and learningoutcomes because it provides the necessary information to meet stakeholders’ decision-makingneeds. In order to gain a better understanding of the strengths and weaknesses of its existing assessment system, Papua New Guinea decided to benchmark thissystem using standardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countries systematically examine and strengthen the performance of different aspects of their education systems. The goal of SABER-Student Assessment is to promote stronger assessment systems that contribute to improved education quality and learning for all.